2010
DOI: 10.1152/ajpheart.00535.2009
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of reactive oxygen species by p53: implications for nitric oxide-mediated apoptosis

Abstract: OO, Kibbe MR. Regulation of reactive oxygen species by p53: implications for nitric oxide-mediated apoptosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 45 publications
3
17
0
Order By: Relevance
“…One more candidate regulator for PRX3 might be p53. p53 showed anti-apoptotic properties by increasing PRX3 expression and decreasing intracellular ROS in vascular smooth muscle cells (Popowich et al 2010), which was in accordance with previous report that low levels of p53 were sufficient for up-regulation of several genes with antioxidant products (Sablina et al 2005). Further investigation is needed to determine the precise links between p53 and PRX3 in cancer cells.…”
Section: Removal Of Ros By Prx3supporting
confidence: 89%
“…One more candidate regulator for PRX3 might be p53. p53 showed anti-apoptotic properties by increasing PRX3 expression and decreasing intracellular ROS in vascular smooth muscle cells (Popowich et al 2010), which was in accordance with previous report that low levels of p53 were sufficient for up-regulation of several genes with antioxidant products (Sablina et al 2005). Further investigation is needed to determine the precise links between p53 and PRX3 in cancer cells.…”
Section: Removal Of Ros By Prx3supporting
confidence: 89%
“…5) is also consistent with the hypothesis that these antioxidant enzymes are mechanistically involved in the crossroads of Cl-amidine and its ability to suppress an oxidative burst. Because Cl-amidine induces p53 Cui et al, 2013) and p53 drives the expression of antioxidant enzymes (Tan et al, 1999;Hussain et al, 2004;Yoon et al, 2004;Bensaad et al, 2006;Popowich et al, 2010;Kang et al, 2013), potentially p53 repression by PADs (either by direct or upstream citrullination) is suppressing the ability of p53 to activate antioxidant enzymes. This hypothesis, though, would have to be tested.…”
Section: Discussionmentioning
confidence: 99%
“…It remains unclear whether these exposures are associated with long-term health effects; however, several epidemiologic studies have raised concerns. For example, acute respiratory illnesses have been reported to occur in 40 -70% of military personnel during deployment (57,69). Compared with nondeployers, deployed military personnel have higher rates of newly reported respiratory symptoms (14% vs. 10%) (65) as well as a greater frequency of new onset asthma (73).…”
Section: Outdoor Air Pollutionmentioning
confidence: 99%
“…The results of their study suggest that prolonged CO exposure may negatively affect SOD and glutathione peroxidase levels, ultimately leading to incapacitated intracellular Ca 2ϩ handling. Popowich et al (57) isolated aortic vascular smooth muscle cells from p53 ϩ/ϩ and p53 Ϫ/Ϫ mouse strains to explore the role of NO in vascular smooth muscle damage. Their study reported that ROS mediate NO-induced vascular smooth muscle apoptosis and showed that p53 protects vascular smooth muscle cells from NO-induced apoptosis by clearing intracellular ROS.…”
Section: Animal Modelsmentioning
confidence: 99%